Making a success of providing NHS Health Checks in community pharmacies across the Tees Valley: a qualitative study - Heywood Peter J; Shucksmith Janet S; Oswald Nigel TA; McNaughton Rebekah J; Watson Pat S (BMC, 2011)
Abstract Background In England and Wales, the Department of Health introduced a primary prevention programme, NHS Health Checks, to provide screening for cardiovascular risk amongst people aged 40-74. The aim of this programme is to offer treatment and advice to those identified with an increased risk of cardiovascular diseases (CVD). The North East of England has some of the highest rates of CVD in the UK and prevention is therefore a priority. NHS Tees funded this programme of work under the local branding of Healthy Heart Checks (HHC). These were initially implemented principally through GP practices from October 2008 but, in order to mitigate the possibility that some hard to reach communities would be reluctant to engage with some primary care settings, plans were also developed to deliver the programme through workplace settings and through community pharmacies. This paper reports specifically on the findings from the evaluation in respect of the setting up of HHCs in community pharmacies and aims to offer some lessons for other service settings where this option is seen as a way of providing low threshold services which will minimise inequalities in intervention uptake. Methods In assessing the community pharmacy component of HHCs, a selection of staff having direct involvement in the process was invited to take part in the evaluation. Interviews were carried out with representatives from community pharmacy, staff members from the commissioning Primary Care Trusts and with Local Pharmaceutical Committee members. Results Evaluation and analysis identified challenges which should be anticipated and addressed in initiating HHC in community pharmacies. These have been categorised into four main themes for discussion in this paper: (1) establishing and maintaining pharmacy Healthy Heart Checks, (2) overcoming IT barriers, (3) developing confident, competent staff and (4) ensuring volume and through flow in pharmacy. Conclusions Delivering NHS health checks through community pharmacies can be a complex process, requiring meticulous planning, and may incur higher than expected costs. Findings from our evaluation provide insight into possible barriers to setting up services in pharmacies which may help other commissioning bodies when considering community pharmacy as a location for primary prevention interventions in future.